Impact of Improved Forage Technology Adoption on Dairy Productivity and Household Income: A Propensity Score Matching Estimation in Northern Ethiopia - Mamaru Tesfaye; Paulos Gutema (Advances in Agriculture)
Adoption of improved forage technologies remains to be one of a promising strategy to boost dairy productivity and enhance household income in many developing countries. However, there are limited rigorous impact evaluation studies on the contributions of such technologies on smallholder dairy productivity and household welfare. This paper examined the impact of improved forage technologies use on smallholder dairy productivity and farm household income in Northern Ethiopia. In this study, a cross-sectional survey design and a multistage stratified sampling procedure were employed. Primary data for the study were obtained from a random sample of 319 rural households, 128 of which are improved forage technology users and the rest are nonusers. The research employed the propensity score matching (PSM) procedure to determine the causal relationship between adoption of improved forage technologies and changes in milk yield and farm household income. Results from PSM revealed that households using improved forage technologies have increased the household milk yield (productivity) by 29.32% and farm income (welfare) by 19.56%. Higher milk yield and annual farm income were compared to those households not using such technologies. Our findings highlight the importance of promoting multiple improved forage technologies among rural smallholder’s dairy producers. Considering this potential, it is suggested that improved forage technology generation, dissemination, and adoption interventions be strengthened for optimum milk production and to attain optimum income under the smallholder farmers’ dairy production system. Moreover, the linkage among research, extension, universities, and farmers needs to be enhanced through facilitating a multistakeholder’s innovation platform.